Impact of various detergent-based immersion and perfusion decellularization strategies on the novel caprine pancreas derived extracellular matrix scaffold - Singh, Garima; Satpathi, Sanghamitra; Gopala Reddy, Bora Venu; Singh, Manish Kumar; Sarangi, Samchita; Behera, Prativa Kumari; Nayak, Bismita (Frontiers in Bioengineering and Biotechnology, 2023)
Limited availability of the organs donors has facilitated the establishment of xenogeneic organ sources for transplantation. Numerous studies have decellularized several organs and assessed their implantability in order to provide such organs. Among all the decellularized organs studies for xenotransplantation, the pancreas has garnered very limited amount of research. The presently offered alternatives for pancreas transplantation are unable to liberate patients from donor dependence. The rat and mice pancreas are not of an accurate size for transplantation but can only be used for in-vitro studies mimicking in-vivo immune response in humans, while the porcine pancreas can cause zoonotic diseases as it carries porcine endogenous retrovirus (PERV- A/B/C). Therefore, we propose caprine pancreas as a substitute for these organs, which not only reduces donor dependence but also poses no risk of zoonosis. Upon decellularization the extracellular matrix (ECM) of different tissues responds differently to the detergents used for decellularization at physical and physiological level; this necessitates a comprehensive analysis of each tissue independently. This study investigates the impact of decellularization by ionic (SDS & SDC), non-ionic (Triton X-100 & Tween-20), and zwitterionic detergents (CHAPS). All these five detergents have been used to decellularize caprine pancreas via immersion (ID) and perfusion (PD) set-up. In this study, an extensive comparison of these two configurations (ID and PD) with regard to each detergent has been conducted. The final obtained scaffold with each set-up has been evaluated for the left-over cytosolic content, ECM components like sGAG, collagen, and fibronectin were estimated via Prussian blue and Immunohistochemical staining respectively, and finally for the tensile strength and antimicrobial activity. All the detergents performed consistently superior in PD than in ID. Conclusively, PD with SDS, SDC, and TX-100 successfully decellularizes caprine pancreatic tissue while retaining ECM architecture and mechanical properties. This research demonstrates the viability of caprine pancreatic tissue as a substitute scaffold for porcine organs and provides optimal decellularization protocol for this xenogeneic tissue. This research aims to establish a foundation for further investigations into potential regenerative strategies using this ECM in combination with other factors.